แนวทางการพัฒนาการบริหารพัสดุให้มีประสิทธิภาพของสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาร้อยเอ็ด - กุตเสนา, ณัฐชัย; นวลสิงห์, ธันยาภรณ์ (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 3 No 3 (2566): กันยายน-ธันวาคม 2566, 2023)
การวิจัยนี้มีวัตถุประสงค์ 1) เพื่อศึกษาสภาพปัจจุบัน สภาพที่พึงประสงค์ และความต้องการจำเป็นในการพัฒนาการบริหารพัสดุให้มีประสิทธิภาพของสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาร้อยเอ็ด 2) เพื่อออกแบบแนวทางการพัฒนาการบริหารพัสดุให้มีประสิทธิภาพของสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาร้อยเอ็ด ปีการศึกษา 2565 จำนวนทั้งหมด 218 คน จำแนกเป็นผู้บริหารสถานศึกษา 60 คน และครู 158 คน เครื่องมือที่ใช้ในการวิจัย คือ แบบสอบถาม สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และค่าดัชนีความต้องการจำเป็น            ผลการวิจัยพบว่า 1. สภาพปัจจุบันและสภาพที่พึงประสงค์ของการบริหารพัสดุของสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาร้อยเอ็ด ค่าเฉลี่ยของสภาพปัจจุบันอยู่ในระดับมาก ส่วนค่าเฉลี่ยของสภาพที่พึงประสงค์อยู่ในระดับมากที่สุด ความต้องการจำเป็นของการบริหารพัสดุ พบว่า ด้านที่มีค่าสูงสุดคือ ด้านการยืมพัสดุ 2. แนวทางการพัฒนาการบริหารพัสดุให้มีประสิทธิภาพของสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาร้อยเอ็ด พบว่า ด้านการวางแผนและจัดหาพัสดุ ได้แก่ จัดทำโครงการใช้พัสดุประจำปี ขอใช้พัสดุตามโครงการ จัดซื้อพัสดุโดยวิธีการตามระเบียบ มีคณะกรรมการตรวจรับพัสดุ ด้านการเก็บ การบันทึกและการเบิกจ่ายพัสดุ ได้แก่ เจ้าหน้าที่พัสดุรับมอบพัสดุ จัดเก็บพัสดุในที่ ๆ ปลอดภัย บันทึกการจัดซื้อพัสดุ เบิกจ่ายพัสดุที่ให้ผู้รับผิดชอบโครงการ จัดทำบันทึกการเบิกพัสดุ ด้านการยืมพัสดุ ได้แก่ จัดทำแบบบันทึกขอยืมพัสดุ ส่งคืนพัสดุต้องตรวจสอบสภาพให้เรียบร้อย มีการติดตามทวงถามให้คืนพัสดุเมื่อเกินกำหนด ด้านการบำรุงรักษาและการตรวจสอบพัสดุ ได้แก่ ดูแลรักษาพัสดุให้พร้อมใช้งานเสมอ พัสดุเกิดความเสียหาย ต้องขอซ่อมแซมพัสดุ และทำประวัติการซ่อมแซมพัสดุ ตรวจสอบพัสดุประจำปีเมื่อสิ้นปีงบประมาณ ด้านการจำหน่ายพัสดุ ได้แก่ พัสดุที่ชำรุด เสื่อมสภาพ ให้ดำเนินการจำหน่ายพัสดุ คณะกรรมการดำเนินการจำหน่ายพัสดุตามความเหมาะสมของแต่ละประเภท รายงานการดำเนินการต่อสำนักงานเขตพื้นที่และสำนักงานตรวจเงินแผ่นดิน This research has the following objectives 1. to study the current situation, desired conditions, and necessary requirements for improving the management of resources efficiently in educational institutions affiliated with the Educational District Office of Roi Et Province. 2.To design guidelines for resource management improvement in educational institutions affiliated with the Educational District Office of Roi Et Province for the academic year 2022. The total number of participants in this research was 218 people, consisting of 60 school administrators and 158 teachers. The research used questionnaires and statistical analysis methods, including percentages, means, standard deviations, and necessity indices.            The research findings are as follows: 1. Regarding the current situation and desired conditions of resource management in educational institutions affiliated with the Educational District Office of Roi Et Province, it was found that the average current situation score was high, while the average desired conditions score was the highest. The area with the highest necessity index for resource management was in the borrowing of resources. 2. Regarding the guidelines for resource management improvement in educational institutions affiliated with the Educational District Office of Roi Et Province, it was found that in the planning and procurement of resources, the institutions have implemented projects for annual resource utilization, procured resources according to regulations, and established committees for resource acceptance. In terms of storage, record-keeping, and distribution of resources, the institutions have ensured safe storage of resources, recorded procurement and distribution, and maintained records of resource distribution. Regarding resource borrowing, institutions have maintained records of resource borrowing, inspected resources upon return, and followed up on overdue resources. In terms of resource maintenance and inspection, institutions have consistently maintained and prepared resources for use, repaired damaged resources, and maintained a history of resource repairs. In terms of resource disposal, institutions have disposed of damaged and worn-out resources and established committees to manage resource disposal as appropriate for each type. Institutions have reported their activities to the Educational District Office and the Office of the Inspector-General at the end of the fiscal year.